2006
DOI: 10.1080/13546780500371241
|View full text |Cite
|
Sign up to set email alerts
|

How reaction time measures elucidate the matching bias and the way negations are processed

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…Confirming Prado and Noveck (2006), participants made significantly more errors and their reaction times were significantly slower when elements in the test item increasingly mismatched with respect to the elements in the rule (see Table 1). This demonstrates that performance in the fMRI scanner is robust.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Confirming Prado and Noveck (2006), participants made significantly more errors and their reaction times were significantly slower when elements in the test item increasingly mismatched with respect to the elements in the rule (see Table 1). This demonstrates that performance in the fMRI scanner is robust.…”
Section: Discussionmentioning
confidence: 56%
“…2 That this particular trial from the truth table paradigm is exceptionally difficult is confirmed by data from standard evaluation tasks in which a participant has to decide whether a provided exemplar is true or false with respect to the rule; the double mismatch case in the falsification condition consistently provides the lowest rates of correct responses (Prado & Noveck, 2006;Evans, 1972). Houdé et al (2000) measured neural activity (using positron emission tomography [PET] methodology) and they were specifically interested in the role of training as participants aimed to avoid errors while searching for a pair of shapes.…”
Section: How Perceptual Mismatches Negatively Affect Normative Reasoningmentioning
confidence: 88%
See 3 more Smart Citations